(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: Education is currently experiencing rapid progress. Very varied learning strategies can make it easier for teachers to apply in order to achieve the goals that have been planned according to the characteristics of students in their school. With the right learning strategies and learning media that are in accordance with the character of students in the classroom, students will experience a fun learning process coupled with varied applications. So the purpose of this study was to see the effectiveness of Problem Based Learning learning strategies assisted by audiovisual media on learning outcomes in social studies subjects. The method in this research is descriptive quantitative. The collection technique applied is in the form of a test. Data analysis techniques in this research are Descriptive Statistics and Inferential Statistics. In this study, using the Moment Product Correlation test and getting the results of 0.516, it turns out that rxy is greater than rtable or 0.516 > 0.456. With a correlation coefficient of 0.516 is significant. Then the results were tested by t-test and got the results of 5,937. From these results, it was then tested with a two-party test so that ttable = t(0,10)(17) = 1.7 turned out to be tcountttable = 5.937 1.7. Based on the test results, it can be concluded that the Problem Based Learning Learning Model assisted by Audio Visual Media on social studies learning outcomes is effective at SD Negeri Jaya Tunggal, TuahNegeri District, MusiRawas Regency. Keywords: Problem Based Learning, Audiovisual Media, Learning Outcomes Abstrak: Pendidikan pada saat ini banyak mengalami kemajuan yang pesat. Strategi pembelajaran yang variatif dapat memudahkan tenaga pengajar untuk mengaplikasikan guna mencapai tujuan yang telah direncanakan sesuai dengan karakteristik siswa di sekolahnya.Dengan adanya strategi belajar yang tepat dan media belajar yang sesuai dengan karakter siswa di kelas, siswa akan mengalami proses belajar yang menyenangkan ditambah dengan penerapan yang beravariatif. Maka tujuan penelitian ini adalah untuk melihat efektifitas strategi belajar Problem Based Learning berbantu media Audio visual terhadap hasil belajar pada mata pelajaran IPS. Metode dalam penelitian ini ialah Deskriptif Kuantitatif. Teknik pengumpulan yang diterapkan adalah berupa tes. Teknik analisis data pada penilitian ini adalah Statistik Deskriptif dan Statistik Inferensial. Pada penelitian ini menggunakan uji Korelasi Produk Moment dan mendapatkan hasil 0,516, ternyata rxy lebih besar dari rtabel atau 0,516 > 0,456.Dengan koefisien korelasi 0,516 adalah signifikan. Kemudian hasil tersebut di uji dengan uji-t dan mendapatkan hasil 5,937. Dari hasiltersebutkemudian di uji dengan uji dua pihak sehingga diperoleh ttabel = t(0,10)(17) = 1,7 ternyata thitung â‰¥ ttabel = 5,937 â‰¥ 1,7. Berdasarkan hasil pengujian dapat disimpulkan bahwa Model Belajar Problem Based Learning berbantu Media Audio Visual terhadap hasil belajar IPS efektif di SD Negeri Jaya Tunggal, Kecamatan Tuah Negeri, Kabupaten Musi Rawas. Kata kunci: Hasil Belajar; Media Audio Visual; Problem Based Learning